2016
DOI: 10.3389/fpsyg.2016.00842
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Internet Addiction Disorder: Is a Diagnosis Feasible or Not?

Abstract: An important international discussion began because of some pioneer studies carried out by Young (a) on the internet addiction disorder (IAD). In the fifth and most recent version of the Diagnostic, and Statistical Manual of Mental Disorders (DSM) there is no mention of this disorder and among researchers there are basically two opposite positions. Those who are in favor of a specific diagnosis and those who are claiming the importance of specific criteria characterizing this behavior and the precise role it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 97 publications
0
59
0
3
Order By: Relevance
“…However, other researchers have questioned the existence of PIU and IAD itself. Musetti et al (2016) revised literature and found that the internet addiction disorder was not univocally defined and that the construct was somehow too broad and generic to be explicative for a diagnosis. Mitchell (2000) expressed his doubts whether PIU was due to some underlying psychiatric co-morbidity and was justifiable as an entity.…”
Section: Historical Perspectivementioning
confidence: 99%
“…However, other researchers have questioned the existence of PIU and IAD itself. Musetti et al (2016) revised literature and found that the internet addiction disorder was not univocally defined and that the construct was somehow too broad and generic to be explicative for a diagnosis. Mitchell (2000) expressed his doubts whether PIU was due to some underlying psychiatric co-morbidity and was justifiable as an entity.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The latest edition of the Diagnostic and statistical manual of mental disorders (DSM-5) formally recognized gambling disorder as a behavioral addiction. In the case of Internet addiction disorder, a consensual definition of what constitutes an excessive use is difficult to reach since using the Internet has become an integral part of modern life (Musetti, Cattivelli, Giacobbi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Telecommunication Union, at the end of 2018, 51.2% of the global population will be using the Internet [1]. Internet Addiction Disorder (IAD) refers to the problematic use of the Internet, including different aspects of its technology, which affects everyday behavior [2], causing health and social problems [3]. Young has proposed the diagnostic criteria for IAD [4], however, the classification is still controversial and it has not been included in The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition yet.…”
Section: Introductionmentioning
confidence: 99%